The European Union building from Public Choice to Ordo, Röpke's and Einaudi's ideas of Europe. (1st April 2020) - Forte, Francesco
Abstract : The first part the article deals with the Public Choice approach to the European Union as a club of sovereign states that decide to share, without losing sovereignty, some segment of their public goods and related power under the subsidiarity principle. It also deals with Ordo, Röpke's and Einaudi's liberal third way between historical capitalism and a competitive market economy, with – at its centre – the people and the civitas humana . The second part presents the dualistic performances of the main countries of the euro area, building on the analysis of eight parameters for the period 2013–18, and discusses the incompleteness of the institutional construct of the European Union. The third part discusses potential solutions to these problems in the light of Ordo, Einaudi's and Röpke's ideas of Europe.